Research to an alternative explaination of redshift - Rota, Luciano (International Journal of Physical Research, 2015)
Is the â€œBig-Bangâ€ really existed? The present research on theoretical base, through a correct and accurate analysis of the Doppler Effect, attempts to state that there is another concrete and sustainable way to understand the phenomenon of redshift, which could eradicate the hypothesis of an expanding universe.